Perception of the quality of life of family caregivers of adults with cáncer. - Escobar, Carmen Liliana (Investigación y Educación en Enfermería, 2025)
Objective. To describe the perception of the quality of life of family caregivers of adult individuals with cancer. Methodology. Descriptive study conducted in 2008 with a convenience sample of 209 caregivers of adults with cancer who attended oncology units in Medellín, Colombia. The instrument proposed by Ferrell et al., was used to measure the quality of life of the family member caring for the patient, which evaluates quality of life through 37 items that integrate their meaning in the: physical (5 items), psychological (16 items), spiritual (9 items), and social (7 items) well-being. The evaluation of each item is conducted through a Likert-type scale from 1 to 4. Interpretation of the total score and by subscale is an inverse relationship between the score and the deterioration of the caregiver’s state. Results. The participants perceive as most affected the dimensions from the physical (83.2%), psychological (80.9%), and social well-being (75.6%) quality of life scale. The spiritual dimension was the least affected (9.1%). Conclusion. Caregivers of adult patients with cancer have a negative perception of their quality of life. Nursing should participate to support these caregivers